2009
DOI: 10.1002/ijc.24175
|View full text |Cite
|
Sign up to set email alerts
|

Acrylamide exposure measured by food frequency questionnaire and hemoglobin adduct levels and prostate cancer risk in the Cancer of the Prostate in Sweden Study

Abstract: Acrylamide, a probable human carcinogen, is formed during the cooking of many commonly consumed foods. Data are scant on whether dietary acrylamide represents an important cancer risk in humans. We studied the association between acrylamide and prostate cancer risk using 2 measures of acrylamide exposure: intake from a food frequency questionnaire (FFQ) and acrylamide adducts to hemoglobin. We also studied the correlation between these 2 exposure measures. We used data from the populationbased case-control stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
50
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 31 publications
10
50
1
1
Order By: Relevance
“…As in our study, no association between acrylamide intake and prostate cancer risk was observed in the Netherlands Cohort Study (7), a Swedish population-based case-control study (16), and an Italian-Swiss hospital-based casecontrol study (9). The Swedish case-control study also did not show any association between hemoglobin adducts of acrylamide and prostate cancer (16). However, as in the present study, the Netherlands Cohort Study showed a nonsignificant inverse relation between acrylamide intake and advanced prostate cancer risk in never smokers (7).…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…As in our study, no association between acrylamide intake and prostate cancer risk was observed in the Netherlands Cohort Study (7), a Swedish population-based case-control study (16), and an Italian-Swiss hospital-based casecontrol study (9). The Swedish case-control study also did not show any association between hemoglobin adducts of acrylamide and prostate cancer (16). However, as in the present study, the Netherlands Cohort Study showed a nonsignificant inverse relation between acrylamide intake and advanced prostate cancer risk in never smokers (7).…”
Section: Discussioncontrasting
confidence: 47%
“…However, positive associations of acrylamide intake with risk of renal cell, endometrial, and ovarian cancers were observed in a cohort of Dutch men and women (6,7). To date, only one prospective study (7) and two case-control studies have examined the relation between acrylamide intake and prostate cancer risk (9,16). We therefore examined the association between acrylamide intake and risk of prostate cancer in a cohort of Swedish men.…”
Section: Introductionmentioning
confidence: 99%
“…The Cancer of the Prostate in Sweden (CAPS) study (Wilson et al, 2009a), included 1 499 incident, prostate cancer cases and 1 130 male controls. The self-administered FFQ included 261 food items, 18 of which were reported to contain AA.…”
Section: Dietary Studies and Cancermentioning
confidence: 99%
“…This prospective cohort study included 47 869 US men interviewed for the first time in 1986 and followed-up to 2006 for a total of 5 025 prostate cancers (642 lethal). Dietary habits and AA intake was assessed as in the companion NHS and NHS II studies (Wilson et al, 2009a). The median of the middle quintile of AA intake was 20.8 µg per day (i.e.…”
Section: Dietary Studies and Cancermentioning
confidence: 99%
“…Dietary acrylamide intake and its relation with the risk of various types of cancer in humans have been studied in few case-control studies (Mucci et al, 2003(Mucci et al, , 2004Pelucchi et al, 2006;Wilson et al, 2009a) and prospective cohort studies (Mucci et al, 2005(Mucci et al, , 2006Olsen et al, 2008;Schouten et al, 2009;Wilson et al, 2009b;Hogervorst et al, 2007Hogervorst et al, , 2008aHogervorst et al, , b, 2009aLarsson et al, 2009a, b, c, d, e). In the case-control studies, no association between acrylamide intake and cancer risk was observed.…”
Section: Introductionmentioning
confidence: 99%